التقنيات الحديثة لحفظ المخطوطات مركز كاشف أل غطاء انموذجا (Journal of the College of Basic Education, 2022)
Many Arab and foreign countries are rich in an inevitable scientific record of the world heritage acquired through generations, and this revolves around a number of manuscripts, which prompted researchers and those interested in cultural heritage, it was necessary for members of society to preserve our prominent scientific heritage, which is the product of what the world has reached. In order to preserve them, the most important modern and innovative methods were chosen, and the Kashif Al-Ghifa Cultural Foundation was chosen, which is concerned with preserving scientific manuscripts. Religion, literature, thought and culture, the city of immortal exploits, urbanization and civilization. The horizons in our Arab and Islamic world have become wide as part of the cultural and historical precursors. The horizons have become wide and many of the Islamic heritage are opened. Accordingly, our study came to shed light on the modern methods of preserving the manuscript used in Kashif Al-Ghita Institution. The study included two axes preceded by an introduction and followed by a conclusion. The first axis came: to clarify the theoretical aspect , while the second axis was devoted to a study: the practical aspect. In conclusion, we ask God to help us in the search for a landmark in the historical city with a prominent scientific heritage.